ANALISIS PENDEKATAN OBJEKTIF PADA CERPEN: DUA LEMBAR JILBAB BUAT AISYAH KARYA MAULANA SATRYA SINAGA - Rezki Antonio F. Ginting; Evi Rizkita Dewi (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This research aims to This research aims to provide an analysis of the short story: Dua Lembar Jilbab Buat Aisyah using the M. H. Abrams approach. In this study, the studies carried out are (1) describing the content of short stories; (2) analyzing the intrinsic elements of short stories: Dua Lembar Jilbab Buat Aisyah. This research uses descriptive qualitative research method. The subject of this research is Short Story: Dua Lembar Jilbab Buat Aisyah by Maulana Satrya Sinaga. The data collection technique uses library and note-taking techniques. Library design is a technique for retrieving the desired information using the methods described. The results showed that in the short story Dua Lembar Jilbab Buat Aisyah Kraya Maulana Satya Sinaga tells the struggle of the main character who works in Japan, as well as his love story with aisyah, in the end aisyah married her own cousin. The characters in the short story are Fathir, Irwan, and Aisyah. This short story uses a mixed plot or flow.